2018
DOI: 10.1002/eji.201747416
|View full text |Cite
|
Sign up to set email alerts
|

miR‐31 regulates energy metabolism and is suppressed in T cells from patients with Sjögren's syndrome

Abstract: Systemic autoimmune diseases are characterized by the overexpression of type I IFN stimulated genes, and accumulating evidence indicate a role for type I IFNs in these diseases. However, the underlying mechanisms for this are still poorly understood. To explore the role of type I IFN regulated miRNAs in systemic autoimmune disease, we characterized cellular expression of miRNAs during both acute and chronic type I IFN responses. We identified a T cell-specific reduction of miR-31-5p levels, both after intramus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…microRNAs (miRs) have been identified as the noncoding RNAs and found to participate in the progression and management of the inflammatory response [8]. Increasing evidence have elucidated that miRs are associated with inflammation in SS patients [9][10][11]. Besides, miR-377 has been found to mediate the proliferation and apoptosis progresses as well as DNA methylation in several malignancies [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…microRNAs (miRs) have been identified as the noncoding RNAs and found to participate in the progression and management of the inflammatory response [8]. Increasing evidence have elucidated that miRs are associated with inflammation in SS patients [9][10][11]. Besides, miR-377 has been found to mediate the proliferation and apoptosis progresses as well as DNA methylation in several malignancies [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, miR-31 was shown to target SIRT3 to inhibit mitochondrial activity [7] and target ACOX1 to disrupt the lipidome profile in OSCC [8]. Other studies reported that miR-31 modulated the metabolic profile by targeting different types of cells [10,11,37]. As NUMB is the direct target of miR-31 and several other oncogenic miRNAs [23,25,26], findings in this work substantiated that miR-31 is an oncogenic miRNA that also modulates complex metabolic regulation in OSCC [7,8].…”
Section: Discussionsupporting
confidence: 74%
“…As for SS, previous studies reported that miR-335 was upregulated in the minor salivary gland of SS patients, and its expression level was inversely proportional to the unstimulated salivary flow rate [26]. In addition, Johansson et al identified miR-31 was reduced in the T cells of SS patients, which supports the autoimmune T cell response during chronic type I IFN exposure [27]. These findings were consistent with our results that miR-335-3p was upregulated, whereas miR-31-5p was downregulated in autoimmune dacryoadenitis rabbits compared to the controls, suggesting these miRs may play a potential role in the pathogenesis of autoimmune dry eye.…”
Section: Discussionmentioning
confidence: 86%